‘Double reduction’ on the development of off-campus discipline training in JiangXi province - Chen, Danyan; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
In July 2021, the General Office of the Central Committee of the Communist Party of China and the General Office of the State Council issued the Opinions on Further Reducing the Burden of Homework and Off-campus Training for Students in the Stage of Compulsory Education, specifically to comprehensively reduce the burden of children’s homework, and also need to reduce the burden of off-campus training. All regions and departments are required to conscientiously implement it in light of actual conditions. In August of the same year, the Office of the Education Supervision Commission of the State Council issued a special notice to report the progress of the implementation of the "double reduction" work in each province every half month. Jiangxi Province followed the opinions of the Party Central Committee and the State Council, actively responded to the double reduction policy, resolutely implemented no examinations and no rankings in the lower grades, implemented unit exercises in the upper grades, and resolutely banned off-campus training in weekend classes, giving children more time after school.